A Study on the Effect of Herbal-acupuncture with HK-1000 Solution on Hyperlipidemia and Arteriosclerosis Induced Rats - Park Chi-Young; Hong Kwon-Eui (Korean Pharmacopuncture Institute, 2008)
Objective&Methods : The purpose of this study is to observe the effects of HK-1000 Herbal-acupuncture solution at GB34(Yangleungchean) on hyperlipidemia and arteriosclerosis in rats. The author performed several experimental items to analyze the levels of various components and enzymes in serum, urine and liver, as well as the histological change of liver and aorta. Results : 1. HK-1000 herbal-acupuncture infusion increased the cell viability rate, DPPH radical scavenging activity and HMG-CoA reductase inhibition rate in rat liver cells. 2. The levels of total cholesterol, free cholesterol, LDL-cholesterol, phospholipid in serum and AI (atherogenic index) were decreased, and the ratio of HDL to TCL(HDL/TCL) and the level of TG in serum were increased as compared with those of the control group. 3. In the HK-1000 group, serum AST and ALT were significantly lower than those of the HG group and saline group. 4. Hepatic GSH and catalase activities were significantly increased as compared with those of the saline group. Conclusions : From the above results, it is suggested that HK-1000 herbal-acupuncture at GB34 has a therapeutic effect on hyperlipidemia and arteriosclerosis.